Efektivitas Media Pembelajaran Interaktif Berbasis Canva terhadap Hasil Belajar Bahasa Inggris Siswa Kelas 1 - Arinda Puspita Sari; Rofiki, Imam (Ed-Humanistics : Jurnal Ilmu Pendidikan, 2024)
Developing interactive learning media based on Canva presents the subject matter of Things in The Classroom and My School, called SIPLAH (Learning Application about Class and School). For most elementary school students, English is a subject that develops communication skills both verbally and in writing, understanding and expressing information. Therefore, interactive learning media was designed as a learning media that is suitable for use because students need a creative and exciting approach. The development research method applied in the research used the Plomp model. This research aims to analyze its validity, practicality, and effectiveness. Validation data was obtained through validation instruments, and practicality data was obtained from distributing questionnaires to students as users of interactive learning media, and effectiveness testing with indicators of achievement of learning outcomes using a One Group Pretest-Posttest design. The results of the research show that the level of validity according to expert validators and users (practitioners) of the interactive learning media developed is declared very valid with a percentage value of 92%, and the student response can be 82%, which is classified as very practical, and the effectiveness test of the interactive learning media developed is stated effective with N-gain test recapitulation results of 0.87. Canva-based interactive learning media can be applied as a practical and flexible supporting learning media independently.